PENGEMBANGAN BUKU AJAR TEMATIK BERBASIS WAHDATUL ULUM BAGI SISWA KELAS V MADRASAH IBTIDAIYAH - Sapri Sapri; Lailatun Nur Kamalia Siregar; Riris Nurkholidah Rambe; Salsabila Hasibuan (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
This research aims to produce and develop thematic textbooks based on wahdatul ulum on theme 6: Human and Animal Organs, sub-theme 1: The Human Body, sub-theme 2: Organs of Humans and Animals, and sub-theme 3: How to Live Humans, Animals, and Plants in class V Madrasah Ibtidaiyah and to determine the feasibility of the developed wahdatul ulum-based thematic textbooks. This development uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research begins with needs analysis, designing teaching materials, then developing teaching materials, then validating by experts, revising the product, after that conducting product trials (implementing) thematic textbooks based on wahdatul ulum on predetermined respondents. The total average value of the validation results from material, media, and language experts shows that thematic textbooks based on Wahdatul Ulum are very appropriate to use with an average percentage gain of 85%. At the try-out phase, two stages were carried out, namely small group tryouts of 6 students and large group tryouts of 25 students, the student response was 92.59% and gave a very good response to the wahdatul ulum-based thematic textbooks used. According to the results of the research, it was concluded that the thematic textbooks based on wahdatul ulum had been tested for validity, practicality, effectiveness and were very suitable for students to use for learning